Evaluation of ryegrass (Lolium sp.) establishment in kikuyu grass (Pennisetum clandestinum) paddocks using zero tillage (2013)
ABSTRACT: Ryegrass seeding may be limited by the lack of farming machinery. The aim of this study was to evaluate the establishment of three ryegrass (Lolium sp.) genotypes (annual diploid, annual tetraploid, and hybrid tetraploid) in kikuyu grass pastures (Pennisetum clandestinum) with seeding based on zero tillage. The first agronomic evaluation of ryegrass was conducted 60 days after seeding and then every 35 days until the fourth grazing. For data analysis we used a linear mixed model with grass genotype, topography, and number of cuts as fixed effects. The random effect was the farm. Biomass and establishment percentage were better in the high area (flat terrain) for the three genotypes (p<0.05). Biomass of annual diploid ryegrass was higher in the high and slope area (p<0.05). The leaf/stem ratio, height, length, and width of the last and fully elongated leaf were statistically significant (p<0.05) between the different cuts for all genotypes, showing that grass growth increases with the number of cuts when rational grazing management is provided. The results of this study support the conclusion that greater adaptation of diploid ryegrass associated with Kikuyu grass positively impacts biomass production under zero tillage.